Pengaruh persepsi wajib pajak dengan pendekatan Technology Acceptance Model terhadap penggunaan E-filing di KPP Pratama Cimahi - Chikita Bela Martunisa; Riauli Susilawaty Hutapea; Neneng Dahtiah (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
ThiswstudybaimsytobdeterminegtheYeffectHof taxpayer perceptions on the use of e-filing with the TechnologyRAcceptanceUModelJ(TAM)Bapproach. As a manifestation ofG e-government in the era of industrialCrevolutionH4.0,Ythe Directorate General ofBTaxes implemented an e-filing program, namely an electronic submission of Income Tax Tax Return (SPT) applications online and in real time. Data in KPP Pratama Cimahi for 2014-2018 shows only around 30% of the target number of taxpayers who report. The success factor in implementing e-filing is the acceptance of taxpayers as users to switch from a manual reporting system to an online reporting system. TAM is an information technology system acceptance model that is used by users to explainHandGpredictBuserYacceptanceBofBa technology. The independent variable is perceived ease ofG use, perceived usefulness, attitudes towards technology use, and interest in using technology on theBdependentVvariableBthe actualBuseBof e-filingCtechnology.VThe researchVmethodNusedVisGquantitativeVmethod. The population of this research is taxpayers who are registered at KPP Pratama Cimahi.CThe sample wasCfeterminedVbyXtheVincidentalsamplingvmethod of 100 respondents.gtThis research databcollectionvmethodciscabquestionnaire,xthevdata xiscprocessed usingcmultipleklinearcregressionTanalysis.CThexresultsdofjthisfstudycindicate that perceived ease ofT use, perceived usefulness, attitudes towards the use of technology, interest inBusing technologyshaveravpositiveheffecthon the actual use of e-filing both partially and simultaneously at KPP Pratama Cimahi.